2011
DOI: 10.1210/en.2009-1037
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Bisphenol A Alters Rat Uterine Implantation-Associated Gene Expression and Reduces the Number of Implantation Sites

Abstract: Endocrine disrupters have been associated with reproductive pathologies such as infertility and gynecological tumors. Using a rat model of early postnatal exposure to bisphenol A (BPA), we evaluated the long-term effects on 1) female reproductive performance, 2) uterine homeobox A10 (Hoxa10) and Hoxa10-target gene expression, and 3) ovarian steroid levels and uterine estrogen receptor α and progesterone (P) receptor expression. Newborn female rats received vehicle, BPA.05 (0.05 mg/kg · d), BPA20 (20 mg/kg · d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 44 publications
4
82
0
2
Order By: Relevance
“…The concentration of phytoestrogens in the diet was not evaluated because food intake was equivalent for control and experimental rats and both groups were exposed to the same levels of phytoestrogens [38]. Two females and one male were housed in a cage.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of phytoestrogens in the diet was not evaluated because food intake was equivalent for control and experimental rats and both groups were exposed to the same levels of phytoestrogens [38]. Two females and one male were housed in a cage.…”
Section: Methodsmentioning
confidence: 99%
“…Bisphenol A (BPA) is known for its action as an endocrine-disrupting compound and a weak estrogen agonist/antagonist. However, BPA is still being used as part of the plastic containers for embryo cultures (Hunt et al 2003, Berger et al 2010, Varayoud et al 2011). Studies indicated a broad range of effects on the embryos upon BPA exposure, such as altered developmental rate and cell death (Ferris et al 2016) and toxicity to the neural progenitor cells (Yin et al 2015).…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Как показали исследования, изменения гло-бального профиля метилирования генома в тканях матки связаны как с нарушением экспрессии генов эстрогено-вых рецепторов, чувствительных к БФА [65,66], и экс-прессии генов в плаценте [67,68], так и изменениями в метилировании ДНК гена Hoxa. При этом трудно точ-но установить, вовлечена ли в этот механизм сниженная активность ДНК-метилтрансфераз (DNMTs), или про-исходит модификация уровня их экспрессии [63,65,68]. Высокий уровень деметилирования ДНК, сопровожда-ющийся повышением экспрессии ряда импринтирован-ных генов, был выявлен в плаценте и в ткани эмбрионов 9,5-го и 12,5-го дня развития.…”
Section: исследование In Vitro уровня метилирования днк при культивирunclassified